2012
DOI: 10.1186/1471-2474-13-141
|View full text |Cite
|
Sign up to set email alerts
|

Early functional results after Hemiarthroplasty for femoral neck fracture: a randomized comparison between a minimal invasive and a conventional approach

Abstract: BackgroundA minimal invasive approach for elective hip surgery has been implemented in our institution in the past. It is widely hypothesized that implanting artificial hips in a minimal invasive fashion decreases surgical trauma and is helpful in the rehabilitation process in elective hip surgery. Thereby geriatric patients requiring emergency hip surgery also could theoretically benefit from a procedure that involves less tissue trauma.MethodsSixty patients who sustained a fractured neck of femur were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 48 publications
4
54
0
2
Order By: Relevance
“…The literature suggests that some of the reported benefits of the direct anterior approach after elective THA may apply to patients undergoing hemiarthroplasty for acute intracapsular femoral neck fractures. [22][23][24][25] The current study showed that patients undergoing the direct anterior approach were more likely to be discharged on postoperative day 3 or earlier (28%) compared with those undergoing other surgical approaches (6%). No difference in the number of feet ambulated during the first 3 postoperative days was noted between groups.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The literature suggests that some of the reported benefits of the direct anterior approach after elective THA may apply to patients undergoing hemiarthroplasty for acute intracapsular femoral neck fractures. [22][23][24][25] The current study showed that patients undergoing the direct anterior approach were more likely to be discharged on postoperative day 3 or earlier (28%) compared with those undergoing other surgical approaches (6%). No difference in the number of feet ambulated during the first 3 postoperative days was noted between groups.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, it remains unknown whether the benefits reported with the direct anterior approach to THA for degenerative arthritis can be extrapolated to a frail elderly population undergoing hemiarthroplasty for femoral neck fractures. [22][23][24][25] The current study reported and compared the results of patients with displaced femoral neck fractures undergoing hemiarthroplasty with the direct anterior approach with patients undergoing an alternative surgical approach. The authors hypothesized that patients undergoing the direct anterior approach would have a shorter length of stay, improved ambulation, and a higher rate of return to baseline ambulatory status without an increase in complications related to the surgical approach.…”
mentioning
confidence: 99%
“…8,20 Alternative surgical approaches such as the anterolateral and direct anterior approaches preserve the posterior structures of the hip, conferring stability to the joint. 21,22 The advantages of THR as treatment for a femoral neck fracture includes the ability to immediately weight bear, and for it to be the definitive treatment of both the fracture and any future conditions such as osteonecrosis or arthritis. The disadvantages include the possibility of dislocation, the functional limitations imposed by a THR, and the more Anteroposterior radiograph demonstrating a minimally displaced femoral neck fracture.…”
Section: Choosing Thrmentioning
confidence: 91%
“…Die Inzidenz für die Gesamtbevölkerung liegt bei etwa 90/100 000 und nimmt ab dem 65. Lebensjahr nahezu exponentiell auf knapp 1000/100 000 zu [7,8]. Zwei Drittel dieser Frakturen betreffen Frauen um das 80.…”
unclassified